Analysis of Citizens' Tax Avoidance Actions Based on Tax Laws in Indonesia - Eriyan Rahmadani Dianova (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Tax avoidance is an effort to avoid taxes that are carried out legally and safely to taxpayers in accordance with applicable tax regulations. This is because the methods and techniques used are based on exploiting the weaknesses contained in the tax laws and regulations. This type of written research method is qualitative depending on the type of document. Qualitative research is a type of research whose results are not based on statistics or other calculations. Application of high tax rates is also an obstacle because it burdens taxpayers. Other disabilities include: Regulations that apply the law are often inconsistent with the law. There are many formal and informal taxes at the central and regional levels. Weak law enforcement, complicated bureaucracy, and so on, will certainly help achieve good governance in the form of clean and authoritative government, if done properly. Indonesia does not yet have strong enough regulations to regulate tax avoidance. This is because Article 18 of Law Number 36 of 2008 concerning the Fourth Amendment to Law Number 7 of 1983 concerning Income Tax only regulates one taxpayer effort to avoid taxes, namely the only application of the concept of transfer pricing. On the other hand, other forms of tax avoidance are not regulated. Therefore, the state needs to reform its tax system.